Artwork in the workplace - Mohamed, Zakiah; Matrahah, Izaddin (2024)
Art plays a major role to stimulate the senses and make people feel good. It is because it serves as a reflection of our inner emotions, evoke our feelings, creating a bridge of understanding between diverse groups of people. Art is also a medium for communicating ideas, telling stories and conveying messages. It can also act as a therapeutic relief by the sharing of experiences and reactions, starting conversations and eventually creating understanding.